Elelwani - Wa Luruli, Ntshavheni; Masabe, Florence; Maumela, T. N., 1924-; Blackboard Trust (Firm); Shadowy Meadows Productions (Firm); Eastwest Film Distribution GwBH ([Pretoria] : Shadowy Meadows Productions, 2012)
Elelwani has just completed her studies. She's been offered a dream job in Chicago, and she's engaged to Vele, the love of her life. They drive through the ever greener countryside into Elelwani's village, where they intend to tell her parents their plans to marry and spend their future together. She's blindsided when her parents reveal shortly afterwards that her hand has been promised to the tribal king. Torn between a growing future and a familial duty, she initially rebels, but finally consents. What happens next is a cinematic initiation into the culture of the Venda and is the first film to be made in this language.
Originally released as a motion picture in 2012.
Based on: Elelwani / Titus Maumela.
Florence Masebe, Ashifashabba Muleya, Sammy Moeti, Samson Ramabulana, Salome Mutshinya, Vusi Kunene.
Cinematographer, Lance Gewer; editor, Aryan Kaganof; music, Christopher Letcher.
In Venda, with optional English subtitles.
Winner of 2 Awards, at the Africa Movie Academy Awards 2013: Best Actress In A Leading Role (Florence Masebe); and, Achievement in Production Design
Keywords: Venda (African people) -- Social life and customs -- Drama; Forced marriage -- Drama; Feature films; Internet videos; Streaming video